Fodor's Tokyo 2025 - Delisle, Jonathan; Farris, Jay; Goss, Rob; Grace, Randy; Morel, Robert (Travel writer); Ziminski, Alexandra (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2025)
"Whether you want to stay in a ryokan, stand in awe at busy Shibuya Crossing, visit beautiful temples, or hike Mount Fuji, the local Fodor's travel experts in Tokyo are here to help! Fodor's Tokyo guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos." --